Fmn2 Regulates Growth Cone Motility by Mediating a Molecular Clutch to Generate Traction Forces. (10th November 2020) - Ghate, Ketakee; Mutalik, Sampada P.; Sthanam, Lakshmi Kavitha; Sen, Shamik; Ghose, Aurnab
Highlights: Neurodevelopmental disorder-associated formin Fmn2 regulates growth cone motility. Fmn2 stabilises adhesive contacts and influences F-actin retrograde flow. Fmn2 modulates the development of traction forces exerted by growth cones. Fmn2 regulates a molecular clutch in growth cones during axonal outgrowth. Abstract: Growth cone–mediated axonal outgrowth and accurate synaptic targeting are central to brain morphogenesis. Translocation of the growth cone necessitates mechanochemical regulation of cell-extracellular matrix interactions and the generation of propulsive traction forces onto the growth environment. However, the molecular mechanisms subserving force generation by growth cones remain poorly characterized. The formin family member, Fmn2, has been identified earlier as a regulator of growth cone motility. Here, we explore the mechanisms underlying Fmn2 function in the growth cone. Evaluation of multiple components of the adhesion complexes suggests that Fmn2 regulates point contact stability. Analysis of F-actin retrograde flow reveals that Fmn2 functions as a clutch molecule and mediates the coupling of the actin cytoskeleton to the growth substrate, via point contact adhesion complexes. Using traction force microscopy, we show that the Fmn2-mediated clutch function is necessary for the generation of traction stresses by neurons. Our findings suggest that Fmn2, a protein associated with neurodevelopmental and neurodegenerative disorders, is a key regulator of a molecular clutch activity and consequently motility of neuronal growth cones.